EFFECTS OF SOME ELEMENTS ON THE GROWTH, AND THE DEVELOPMENT OF BANANA SHOOTS (M. acuminata) IN MICROPONIC SYSTEM - Thi Thu Huong, Bui; Dong (Journal of Forestry Science and Technology, 2020)
Tieu Hong banana variety (Musa acuminata) is one of the most popular bananas in Vietnam because they have not only beautiful colour, delicious taste but also high nutrition, and significantly economical value. Nowadays, this banana variety is primarily propagated in wide-scale by micropropagation which is effective with a high propagation coefficient, thus, that can meet the increasing demand of people to enjoy it. However, the method of propagation still has some limitations such as the low quality of the plantlets, the quite high cost in producing. Whereas, the micro-hydroponic (also called microponic) system is said as a promising technique that can improve the efficiency of the multiplication of many plant species in vitro. Therefore, this technique can improve the Tieu Hong banana micropropagation in vitro. With using plant growth regulators, the appropriate volume, and identifying the suitable density of shoots per a culturing box, and supplementing silver nanoparticles in the system, the microponic culturing system was successfully applied on the Tieu Hong banana shoots. These experimental results showed that Tieu Hong banana shoots cultured in the system added with specific conditions gained some positive effects with the remarkable data observed. Specifically, the average number of roots was about 4 roots/shoot, the root length was approximately 2.2 cm. Also, the addition of nano silver at a concentration of 4 ppm gave the significant results of in vitro Tieu Hong banana rooting with an average root number of 5.13 roots/shoot and an average root length of 4.01 after 2 weeks of culture.